Correlation between Chemokine Receptor CXCR4 Expression and Prognostic Factors in Patients with Prostate Cancer - Jung, Seok Jin (The Korean Urological Association, 2011)
PURPOSE: We evaluated the correlation between the expression of CXCR4 and prognostic factors in patients with prostate cancer. MATERIALS AND METHODS: A total of 57 patients who had undergone surgery for prostate cancer were enrolled. Specimens were obtained before any treatment and were stained with antihuman CXCR4 antibody. The intensity of staining was graded as low or high. The age, pretreatment prostate-specific antigen (PSA) level, Gleason score, T stage, biochemical recurrence, local recurrence, and distant metastasis were compared according to the expression of CXCR4 in patients with prostate cancer. RESULTS: Local recurrence was higher in the group with high expression, in 11 of 36 cases (30.6%), than in the group with low expression, in 1 of 21 cases (4.8%), with statistical significance (p=0.040). Distant metastasis was also associated with expression, occurring in 10 of 36 cases (27.8%) in the group with high expression and in 1 of 21 cases (4.8%) in the group with low expression (p=0.041). In the logistic regression test, CXCR4 expression was the only factor in determining local recurrence (p=0.016) and distant metastasis (0.022). Furthermore, the group with high CXCR4 expression showed significantly longer cancer-specific survival than did the low expression group (p=0.041). CXCR4 showed no association with age (p=0.881), pretreatment PSA level (p=0.584), Gleason score (p=0.640), T stage (p=0.967), or biochemical recurrence (p=0.081). CONCLUSIONS: The high expression of CXCR4 was associated with local recurrence and distant metastasis. CXCR4 expression was shown to be a useful prognostic factor for patients with prostate cancer.